Interacções, reflexos e projecções : poéticas dos materiais e das técnicas na obra de José Rodrigues - Soares, Maria Leonor Barbosa (2009)
The art work of José Rodrigues has been taking shape in various art fields: drawing, sculpture, scenography, medal work, ceramics, engraving, and illustration. The analysis of the mechanisms through which the communicative potential of the different materials is revealed can be found across all the fields he has been practising in. As a demand and as a consequence of the attention given to materials, we acknowledge the artist’s involvement in a process that continually recovers, recreates and projects questions, suggested, in turn, by the ways in which the materiality is experienced; consequently, the material structures that the questions previously bore a reference to are re-elaborated. This essay is a reflection on the above mentioned mechanisms within the fields of drawing and sculpture and, in brief final remarks, of scenography and medal work as well.